Linkages of financial groups in the European Union : financial conglomeration developments in the old and new member states - Ulst, Ingrid (Central European University Press, 2005)
Annotation Financial services industry has shown trends of increased consolidation across different types of financial institutions. This book focuses on the conglomeration of banking and insurance activities among financial instituations of the 15 old members of the European Union, and addresses the development and impact of conglomeration linkages between these fifteen and the ten new member states.
Keywords: Financial services industry -- European Union countries.; Conglomerate corporations -- European Union countries.; Services financiers -- Pays de l'Union européenne.; Conglomérats (Économie politique) -- Pays de l'Union européenne.; BUSINESS & ECONOMICS -- Finance.; Conglomerate corporations; Financial services industry; European Union countries; Bankwezen.; Verzekeringswezen.; Conglomeraten (economie); 21st century, Banks, Economic integration, European Union, Financial services, Late 20th century.